Pengaruh Stres Kerja, Beban Kerja dan Lingkungan Kerja terhadap Turnover Intention pada Karyawan Bagian Produksi - Hanum Indriati, Inayat; Dyah Herdiany, Hapsari; Satya Putri, Aulia (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
This study aims to determine the effect of work stress, workload, work environment, and turnover intention. This research was conducted in June 2023 – October 2023 at sugar factory in Yogyakarta. This research is a quantitative research with the number of respondents 67 employee and the sampling technique using simple random sampling. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially work stress and workload has a positive effect on turnover intention. The work environment has a negative effect on turnover intention. Simultaneous test results show that work stress, workload and work environment have a significant effect on turnover intention.